Monetary policy and inflationary shocks under imperfect credibility - Matthieu Darracq Pariès; Stéphane Moyen (European Central Bank (ECB), 2009)
This paper quantifies the deterioration of achievable tabilization outcomes when monetary policy operates under imperfect credibility and weak anchoring of long-term expectations. Within a medium-scale DSGE model, we introduce through a simple signal extraction problem, an imperfect knowledge configuration where rice and wage setters wrongly doubt about the determination of the central bank to leave unchanged its long-term inflation objective in the face of inflationary shocks. The magnitude of private sector learning has been calibrated to match the volatility of US inflation expectations at long horizons. Given such illustrative calibrations, we find that the costs of aintaining a given inflation volatility under weak credibility could amount to 0.25 pp of output gap standard deviation.
Keywords: E4; E5; F4; 330; Imperfect credibility; monetary policy; Signal extraction; Geldpolitik; Glaubwürdigkeit; Inflationssteuerung; Inflationserwartung; Dynamisches Gleichgewicht; USA